Ferramentas algébricas para o estudo do entrelaçamento quântico - Oliveira, João Luzeilton de (2012)
This thesis presents some results about two important subjects of the quantum information theory: quantum entanglement and quantum algorithms. Regarding the entanglement, a relationship between negativity and minors principals of Hermitian matrices was stablished, allowing the analysis of the entanglement of two qubits states, three and four qubits pure states, using the minors principals. It was also proposed a new measure, using negativity, for calculating the entanglement of pure states of six qubits. Finally, with respect to quantum algorithms it was proposed a quantum search algorithm able to finding the minimum of a function by performing only one measurement. The algorithm is described and an example of its usage in the calculation of the period of a periodic function is presented.